Ethical and Legal Aspects of the Dispute Over the Legalization of Assisted Suicide in Italy in 2017-2022 - Kobyliński, Andrzej (Studia Ecologiae et Bioethicae, 2023)
The main purpose of the study undertaken in this paper is a synthetic presentation of the major stages of the dispute over the legalization of assisted suicide in Italy as well as an analysis of selected ethical and legal aspects related to this issue. Assisted suicide is medical and administrative aid provided to a person who has decided to take their own life. It differs from direct euthanasia in the fact that the final act of taking one’s own life, involving deliberate administration of the necessary substances is performed entirely by the patient themself without interference of any third parties. In 2017, the institution of the living will was introduced in Italy, which allows to make a declaration of intent for potential future loss of consciousness and ability to make decisions regarding one’s treatment and saving one’s life. In 2019, the Constitutional Court obliged the parliament to draft a law regulating the termination of life on request. In March 2022, the relevant provisions were voted in the Chamber of Deputies. They were then forwarded to the Senate. Ultimately, this bill was not passed, due to the collapse of the government in July 2022 and the dissolution of the parliament. The conducted analyses showed that the Italian ethical and legal dispute regarding the legalization of assisted suicide is an important element of the contemporary global debate, concerning, among others, medical ethics, value and quality of human life, conscience clause, ethical aspects of suffering and death.